2014
DOI: 10.3389/fphys.2014.00452
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metabolic remodeling in response to endurance exercise in salmonids

Abstract: Phenotypic plasticity of skeletal muscle is relevant to swimming performance and metabolism in fishes, especially those that undergo extreme locomotory feats, such as seasonal migration. However, the influence of endurance exercise and the molecular mechanisms coordinating this remodeling are not well understood. The present study examines muscle metabolic remodeling associated with endurance exercise in fed rainbow trout as compared to migrating salmon. Trout were swum for 4 weeks at 1.5 BL/s, a speed similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…68 Under multiple stressors, including increased exercise, enzyme levels like HK are known to increase in salmonids. 69 As with LDH, it was quite similar across treatments in the current study. The only difference was regarding fasted CUC fish, with approximately twice the values compared with RFC and CON.…”
Section: Muscle Enzyme Activitysupporting
confidence: 59%
See 1 more Smart Citation
“…68 Under multiple stressors, including increased exercise, enzyme levels like HK are known to increase in salmonids. 69 As with LDH, it was quite similar across treatments in the current study. The only difference was regarding fasted CUC fish, with approximately twice the values compared with RFC and CON.…”
Section: Muscle Enzyme Activitysupporting
confidence: 59%
“…HK enzyme is responsible for initiating the glycolytic pathway 65 and is used as an indicator of carbohydrate use, helping to keep blood glucose levels stable 68 . Under multiple stressors, including increased exercise, enzyme levels like HK are known to increase in salmonids 69 . As with LDH, it was quite similar across treatments in the current study.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, the same study showed that mitochondrial activity and CS in particular are down-regulated by multiple sensory perception stressors. White muscle CS activity also increases under moderate activity in zebrafish (Danio rerio) (McCelland et al 2006), but a significant reduction has been observed in rainbow trout after four weeks at 1.5 BL•s -1 (Morash et al 2014), which demonstrates a complex and sometimes contradictory regulation. In exercised brown trout (Salmo trutta), the COX activity of skeletal muscle also increased at a low velocity (42% of maximal swimming capacity), but decreased when the swimming capacity increased to 83% of maximal capacity (Antilla et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the effects of exercise likely depend on muscle metabolic phenotype. For instance, exercise has a stronger influence on red muscle phenotype, as compared to white muscle in salmonids (Morash et al, 2014 ). Similarly, uphill-, as compared to down-hill training enhanced mitochondrial function specifically in both soleus and vastus intermedius skeletal muscle (Schlagowski et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%